LEKSIKON PENGRAJIN SEPATU DI DESA JOHOWINONG KABUPATEN JOMBANG: KAJIAN SEMANTIK - Mila Rahma Cahyaningrum; Yuli Astuti, Eka; Nur Fateah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lexicon of shoemakers, as part of local knowledge, is at risk of being lost due to modern industry development and the lack of scientific documentation. This study aims to describe the forms of the lexicon and analyze the lexical and cultural meanings contained within it through semantic analysis. Theoretically, this study employs morphological theory to classify monomorphemic and polymorphemic forms, Lyons’ semantic theory for denotative lexical meaning, and Geoffrey Leech’s theory for cultural meaningthrough the concept of associative meaning. This study employs a qualitative descriptive method. Data were collected through observation, in-depth interviews, note-taking, and audio recordings of active shoemakers in Johowinong Village, and were then analyzed based on the categories of tools, materials, and work processes, as well as lexical form classifications. The results of the study show that there are 43 lexical items consisting of 31 monomorphemic and 12 polymorphemic terms, grouped into 8 tool lexical items, 23 material lexical items, and 12 work process lexical items, for example, mal [mal] (tool), kalêp [kaləp] (material), and ngêmal [ŋəmal] (process). All lexical items possess denotative meanings that directly refer to functions in shoe production. Cultural meanings are found in some lexical items, such as klêbut, which reflects traditional craftsmanship; pom, which refers to knowledge of material mixtures; and sèrèan, which signifies the value of material efficiency. These findings indicate that the shoemaking lexicon is not merely technical but also represents the relationship between language, meaning, and work culture that has been passed down through generations